Union Power and the Public Interest - Boivin, Jean (Relations industrielles / Industrial Relations, 1974)
This article reviews "Union Power and the Public Interest" by Emerson P. Schmidt.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Politics and the Labor Movement in Chile - Boivin, Jean (Relations industrielles / Industrial Relations, 1974)
This article reviews "Politics and the Labor Movement in Chile" by Alan Angell.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Employeurs-employés - Boivin, Jean (Relations industrielles / Industrial Relations, 1974)
This article reviews "Employeurs-employés" by J. Finkelman.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z